The effect of the Environmental Protection Agency maximum contaminant level on arsenic exposure in the USA from 2003 to 2014: an analysis of the National Health and Nutrition Examination Survey (NHANES). (November 2017) - Nigra, Anne E; Sanchez, Tiffany R; Nachman, Keeve E; Harvey, David E; Chillrud, Steven N; Graziano, Joseph H; Navas-Acien, Ana
Summary: Background: In 2006, the current US Environmental Protection Agency (EPA) maximum contaminant level for arsenic in public water systems (10 μg/L) took effect. We aimed to assess national trends in water arsenic exposure in the USA, hypothesising that urinary arsenic concentrations would decrease over time in individuals using public water systems but not in those using well water (which is not federally regulated). We further estimated the expected number of avoided skin or lung and bladder cancer cases. Methods: In this analysis of the 2003–14 cycles of the National Health and Nutrition Examination Survey (NHANES), we used data for dimethylarsinate (DMA), the main metabolite of inorganic arsenic in human beings, and total urine arsenic to reflect water arsenic exposure in survey participants. To isolate exposure to water arsenic, we expanded a residual-based method to remove tobacco and dietary sources of urinary DMA and total arsenic. We also applied EPA risk-assessment approaches to estimate the expected annual number of avoided skin or lung and bladder cancer cases comparing arsenic exposure in 2013–14 with 2003–04. Findings: We obtained data from 14 127 individuals who participated in the NHANES between 2003 and 2014. Among public water users, fully adjusted geometric means of DMA decreased from 3·01 μg/L in 2003–04 to 2·49 μg/L in 2013–14 (17% reduction; 95% CI 10–24; p-trend<0·001); no change was observed in well water users (p-trend=0·35). Assuming these estimated exposure reductions will remain similar across a lifetime, we estimated a reduction of 200–900 lung and bladder cancer cases or 50 cases of skin cancer per year depending on the approach used. Interpretation: The decrease in urinary arsenic observed in public water but not private well users in NHANES 2003–14 suggests that the implementation of the current maximum contaminant level regulation is associated with reduced arsenic exposure in the US population. Our study suggests that well water users are inadequately protected against drinking water arsenic, and supports the crucial role of federal drinking water regulations in reducing toxic exposures and protecting human health. Funding: The National Institute of Environmental Health Sciences.